Stock market linkages: Implications for Chinese mainland investors - Wu, Xiaojing (Université d'Ottawa | University of Ottawa, 2003)
This paper examines long-run relationship and short-run dynamics among US, Japan, Singapore, Hong Kong, Taiwan, and South Korea stock market indices by using Johansen's FIML methodology and estimating a first-differenced VAR model. Because of the nonstati